Sistema de controle em malha fechada para um sistema de irrigação por gotejamento - Ferreira, Marcos Alves (2012)
This work aims to develop a closed loop control system in a drip irrigation system, aimimg to control irrigation process. The system was deployed in ​​Low Acaraú Irrigation District (DIBAU) in an area of 1.0 ha, planted with watermelon, divided into four sub0areas, with three capacitive sensors for soil moisture installed at three depths (0.15 m, 0.30 m and 0 were installed , 45m.The sensor was 0.15 m connected to a programmable logic controller (PLC), for driving the valves and the acceleration / deceleration the motor by a frequency converter according to the number of actuated valves simultaneously. The sensors other depths were used to monitor soil moisture along the profile. Using predefined calibration equations, the readings of the capacitive sensors in Hertz were convertd to volume based soil moisture and following initial parameters defined: field capacity soil (CC), at 20%, as the set point (target) of control,conrolling treatments of 820, 795, and 795 Hz, for plots E1, E2 and E4, respectively, to activate the pump, and 732, 714, and 751 Hz to turn the pump off. In a second stage, control parameters were 784 and 795 Hz for stations E1 and E2, respectively, to activate the púmp and 751 Hz and 762 to turn off the system. The control systems sucessfully controlled soil moisture, maintaining soil moisture at derired levels with a high frequency of irrigation. From the readings of capacitive sensors converted into moisture on a volume basis and through a calibration equation, we defined the initial parameter of soil to drive the pump and 751 and 762 Hz to shutdown. It was found that the system showed satisfactory performance, maintaining soil moisture levels at high frequency irrigation.